Bilateral internal globus pallidus stimulation for the treatment of spasmodic torticollis. - Parkin, S; Aziz, T; Gregory, R; Bain, P (2001)
Three patients with spasmodic torticollis (ST) obtained substantial benefit from bilateral globus pallidus internus (GPi) stimulation. Progressive improvement in ST occurred over several months but residual cervical dystonia remained. These results corroborate those obtained by Krauss et al. on three patients with ST.